Role of Accounting Information in Decision-Making Process, the Importance for its Users - Berisha Vokshi Nexhmie; Xhelili Florentina Krasniqi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Overall economic development of the country, beside it, requires adequate information, reliable and important for economic decisions from investors, managers, administrators of state, etc. Along with other economic development and management, also and development of an accounting system, able to provide the necessary information and reliable in decision-making, is an important factor. Qualitative and reliable financial information is a key element in decision-making process, while the availability of such information has special importance for business management and is public interest with priority in general. The role of this information is important, not only for foreign investors or large businesses, but even for those small and medium because it provides important information about the phases of decision-making, such as planning, control and evaluation. The aim of this study is to provide an overview of developments and knowledge on accounting information and the influence that it has on decision-making, needs that management has for information and how they are realized currently, in order to see accounting information as one of the important directions of increase of efficiency on decisionmaking of direction of economic units (entities) and users of accounting information. Through descriptive statistical analysis the importance of high quality accounting information and its impact on decision-making by its users will be presented. We conclude that the information is an indispensable resource for the development of successful and efficient business. The information communicated by accounting is very important for its users, because it will affect on making an economic decision. This information must meet the qualitative characteristics, so we have to be accurate, valid and useful so that users trust its quality and authenticity. An exact information will reflect in a reliable financial reporting and this will result in strengthening the financial position of the entity, will identify risks and will manage them on time , will enable the attraction of investments, then decisions will be taken on the basis of strong economic information.
Keywords: M41; 330; accounting information; the entity; the economic decision-making; accounting; financial reporting